MPPT Monitoring System of Single Axis Solar Tracker using IOT Technique - A Geetha, S Usha, T M Thamizhthentral, Varun Sah, Aaditya Singh Rana, Aahelee Bandopadhyay (International Journal of Advanced Science and Technology, 2020)
To enable extraction of maximum power obtained by solar panel by using MPPT with P&O algorithm. This project enlightens the use of single axis solar tracker using arduino Uno. An important aspect for monitoring, supervising and performances evaluations of integration of Internet of Things (IOT) technology which is an effective wireless communication technology which overcomes the problems faced in manual monitoring of solar photovoltaic (PV) and getting the values of voltage and current.